Impact of autologous stem cell transplantation on survival outcomes in patients with peripheral T cell lymphoma - TOPTAŞ, TAYFUR; ORUÇ, ÖZEN; ERCAN, TARIK (My University, 2022)
© 2022 Elsevier LtdData about the timing of autologous stem cell transplantation (ASCT) in peripheral T cell lymphoma (PTCL) are conflicting. We aimed to investigate the impact of the sequence of ASCT on the survival outcomes in patients with PTCL. Analyzes were performed retrospectively in a total of 81 patients, 16 of whom underwent upfront ASCT and 12 received salvage ASCT. In univariate analysis, upfront ASCT reduced the risk of progression and death by 77% (Hazard ratio (HR): 0.23, 95% confidence interval (CI): 0.09–0.60) (p = 0.003) and by 84% (HR: 0.16, 95% CI: 0.5–0.55) (p = 0.003), respectively. However, in multivariate analysis, only salvage ASCT predicted a more favorable progression-free and overall survival (HR: 0.17, 95% CI: 0.06–0.48, p = 0.001 and HR: 0.20, %95 GA: 0.06–0.62, p = 0.005, respectively). In conclusion, regardless of first-line therapy, patients have more favorable outcomes if they receive salvage ASCT. Upfront ASCT does not add clinically significant benefit to survival outcomes.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY; Autologous stem cell transplantation; Peripheral T cell lymphoma; Prognosis of peripheral T cell lymphoma